2012
DOI: 10.4236/ojbd.2012.24015
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Morphine and Fentanyl for Stomatitis in Patients Receiving Allogeneic Hematopoietic Cell Transplantation—A Single Center Retrospective Analysis

Abstract: Opioids are widely used as analgesics for oral mucositis in allogeneic hematopoietic cell transplantation (allo-HCT). Their main adverse events are nausea, vomiting, constipation, psychological symptoms, and respiratory depression. In our institute, continuous intravenous morphine was generally used until 2007, followed by intravenous fentanyl as the first-line agent because of its potential fewer adverse events. We retrospectively analyzed 99 patients who underwent allo-HCT in the University of Tsukuba Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it should have a weak influence on bowel motility. It was also reported that fentanyl increases mesenteric blood flow and has a little effect on gastrointestinal function [ 35 , 36 ]. These findings support our data showing that fentanyl is not a risk factor for late defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should have a weak influence on bowel motility. It was also reported that fentanyl increases mesenteric blood flow and has a little effect on gastrointestinal function [ 35 , 36 ]. These findings support our data showing that fentanyl is not a risk factor for late defecation.…”
Section: Discussionmentioning
confidence: 99%